The change in haemoglobin concentration between the first and third trimesters of pregnancy: a population study - Churchill, D; Nair, M; Stanworth, S; Knight, M (BioMed Central, 2019)
BACKGROUND: The physiological fall in haemoglobin concentration from the 1st to the 3rd trimester of pregnancy is often quoted as 5 g/L. However, other studies have suggested varying levels of fall between 8 and 13 g/L. We evaluated the change in haemoglobin concentration between the 1st and 3rd trimesters of pregnancy in a multi-ethnic population of pregnant women. METHODS: A retrospective cohort analysis of 7054 women with singleton pregnancies, giving birth during 2013-15 in a single urban maternity unit in England. We calculated the changes in haemoglobin concentration from 1st to 3rd trimester using the first trimester haemoglobin as the reference point. The population was stratified into sub-groups to explore any differences that existed within the population. RESULTS: In general the fall in haemoglobin concentration was in the order of 14 g/L or 11% of the first trimester value. This fall was consistent for the majority of sub-groups of the population. The fall was lower (7.7%) in the most deprived section of the population, IMD1, but it increased to 11.7% when we restricted that sub-group to pregnant women without health problems during the index pregnancy. Conversely, there was an increase in haemoglobin of 10.2% in women whose first trimester haemoglobin concentration was in the lowest 5% of the total study population. The population fall in haemoglobin was 10.2 g/L (7.8%), after excluding cases above the 95th and below the 5th centiles, and women with a medical and/or obstetric disorder during the pregnancy. CONCLUSION: The fall in haemoglobin during pregnancy is in the order of 14 g/L or 11% of the first trimester level. This is 2 to 3 times higher than suggested by some guidelines and higher than previously published work. The results challenge the current accepted thresholds for practice, and have broader implications for diagnosis and managment of antenatal anaemia. Fall in haemoglobin across pregnancy is around 14 g/L (11%) and significantly higher than previously stated in the pregnant population. This poses questions over currently accepted thresholds for anaemia in pregnancy.